Sonolência diurna excessiva, duracão do sono e permanência em dispositivos eletrônicos em adolescentes: análise de coorte de nascimento (RPS), São Luís-Ma, Brasil. - BARBOSA, Sara Machado Miranda Leal (2019)
INTRODUCTION: Excessive daytime sleepiness (EDS) affects up to 40% of children and adolescents. EDS is characterized by increased sensation of sleep need and decreased alertness, and it is one of the main effects of reduced sleep duration or low-quality sleep. Puberty is a critical period for the transition from childhood to adulthood, affecting sleep. Therefore, it is necessary to study the factors associated with the causes of EDS and duration of sleep among adolescents. OBJECTIVES: To estimate the prevalence and factors associated with excessive daytime sleepiness (EDS) and to assess whether longer time spent on electronic objects is associated with sleep duration in adolescents from the São Luís Birth Cohort (1997/1998) in Brazil. METHOD: Cross-sectional study with 2,505 adolescents, aged 18 and 19, who are part of a third stage of birth cohort collection, which is included in the study “Determinants throughout the life cycle of obesity, precursors of chronic diseases, human capital and health mind.” To estimate the prevalence and factors associated with EDS, a hierarchical modeling was used and the prevalence ratio was calculated using Poisson regression with robust variance adjustment. The sociodemographic characteristics of the adolescent (gender, skin color, economic class, religion, parental marital status), lifestyle (leisure, smoking, alcohol consumption, illicit drug use, caffeine and energy drink consumption, physical activity, body adiposity, screen time and depression) and sleep-related factors (subjective sleep quality, sleep latency, sleep duration, sleep efficiency, sleep disorders, sleep medication use, dysfunction during the day). To assess the association between length of stay in electronic objects and sleep duration, the longest use of electronics (≥ 5 hours per day) and the outcome variable sleep duration were considered as exposure variables. The theoretical model was defined with the aid of Targeted Acyclic Graph and adjustment was used for the following variables: gender, age, education, whether working or studying, marital status and economic class, based on the application of the back-door criterion. The association between longer screen time and sleep time was evaluated by linear regression with and without weighting by the inverse of the probability of exposure by propensity score. RESULTS: The prevalence of EDS was 36.8%. Female gender (PR = 1.33; CI = 1.19-1.49), high risk for alcohol consumption (PR = 1.26; CI = 1.09-1.46), current major depressive episode ( PR = 1.26; CI = 1.08-1.46), sleep disorders with scores from 10 to 18 (PR = 1.43; CI = 1.85), and daily dysfunction with score 5 to 7 (PR = 2.51; CI = 2.06-3.07) were risk factors for EDS. Economic class D/E was a protective factor for EDS (PR = 0.47; 0.27-0.85). The percentage of screen time greater than five hours was 65.9%. On average, adolescents slept 436.1 minutes a day. Adolescents who had screen time greater than five hours a day had 10.3 minutes of less sleep time (CI = -18.6; -1.9) in the unadjusted linear regression analysis, 9.4 minutes in the adjusted linear regression analysis (CI = -18.6; -1.9), and less 9.5 minutes in the weighted analysis of the inverse exposure probability (CI = -18.4; -0.6). More than a third of adolescents have EDS. Those at higher risk need to improve their lifestyle and sleep so that they improve their quality of life and no longer have EDS. Longer use of electronics was associated with shorter time.of sleep among adolescents.